Connection of Social Policy Implementation with the Dynamics of Social Orphanhood in Russian Regions - Bronnikova, Evgeniya M. (2020)
The problem of social orphanhood is one of the most important fmong the social problems of modern Russia, it is acute for a society. In the study of the problems of social orphanage, we used the author’s methods of ranking the regions of Russia according to the dynamics of indicators, an integrated index of “favorable” changes, as well as rating data and indicators of the development of regions of Russia implemented by subjects of social policy and the system of protecting children's rights. Based on the results of the study, the main problems in the social protection of families and citizens in difficult situations are identified. The problems lie in the areas of financial security of social programs, legislative regulation, information support. The results of the study can be used in the activities of social support services. The preventive of social orphanage should be measures of an active social policy.